2022
DOI: 10.1177/15910199221133170
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging approach for the diagnosis of intracranial atherosclerotic disease (ICAD): Basic principles, current and future perspectives

Abstract: Purpose To review the different imaging modalities utilized in the diagnosis of Intracranial Atherosclerotic Disease (ICAD) including their latest development and relevance in management of ICAD. Methods A review of the literature was conducted through a search in google scholar, PubMed/Medline, EMBASE, Scopus, clinical trials.gov and the Cochrane Library. Search terms included, “imaging modalities in ICAD,” “ICAD diagnostic,” “Neuroimaging of ICAD,” “Evaluation of ICAD”. A summary and comparison of each modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…Additionally, transcranial Doppler may also provide estimations of arterial stenosis. 6 While DSA, CTA, and MRA directly measure the lumen to determine stenosis, transcranial Doppler indirectly estimates stenosis by assessing blood flow velocity. 2 7 DSA provides detailed information about the anatomy, severity of the stenosis, and collateral circulation of the intracranial arteries.…”
Section: Determination Of Degree Of Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, transcranial Doppler may also provide estimations of arterial stenosis. 6 While DSA, CTA, and MRA directly measure the lumen to determine stenosis, transcranial Doppler indirectly estimates stenosis by assessing blood flow velocity. 2 7 DSA provides detailed information about the anatomy, severity of the stenosis, and collateral circulation of the intracranial arteries.…”
Section: Determination Of Degree Of Stenosismentioning
confidence: 99%
“…Bash et al studied 115 diseased arterial segments where CTA demonstrated higher sensitivity (98% vs 70%) and a positive predictive value (93% vs 65%) than TOF MRA for detecting intracranial stenosis. 23 It is important to note that, like DSA, MRA is a luminal modality and by itself cannot provide information about the arterial wall and may be susceptible to motion artifacts due to longer acquisition times, 6 potentially affecting image quality and diagnostic accuracy. However, MRA has the advantage that a HR-MRI protocol including T2, T1 and T1 post Gd sequences can be performed during the same session and increase the detection and characterization of plaques.…”
Section: Neuroimagingmentioning
confidence: 99%